2020
DOI: 10.1111/spol.12577
|View full text |Cite
|
Sign up to set email alerts
|

Punitive benefit sanctions, welfare conditionality, and the social abuse of unemployed people in Britain: Transforming claimants into offenders?

Abstract: A defining feature of U.K. welfare reform since 2010 has been the concerted move towards greater compulsion and sanctioning, which has been interpreted by some social policy scholars as punitive and cruel. In this article, we borrow concepts from criminology and sociology to develop new interpretations of welfare conditionality. Based on data from a major Economic and Social Research Council‐funded qualitative longitudinal study (2014–2019), we document the suffering that unemployed claimants experienced becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 54 publications
2
74
0
6
Order By: Relevance
“…Within the last half century, since it was rolled out, it has shaped and been shaped in various areas of everyday life deliberately in order to create and foster this hegemony. Wacquant (2009) shows how it took masses under control though restructuring the incarceration in the USA, while Wright et al. (2020) argues how dismantling the welfare state and replacing it with the neoliberal universal credit system create behavioural changes by sanctions targeting the unemployed.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last half century, since it was rolled out, it has shaped and been shaped in various areas of everyday life deliberately in order to create and foster this hegemony. Wacquant (2009) shows how it took masses under control though restructuring the incarceration in the USA, while Wright et al. (2020) argues how dismantling the welfare state and replacing it with the neoliberal universal credit system create behavioural changes by sanctions targeting the unemployed.…”
Section: Discussionmentioning
confidence: 99%
“…anger, frustration and humiliation; and low mood, anxiety and depression (Peters & Joyce, 2006;Saunders, Stone, & Candy, 2001;Vincent, 1998). This evidence is supported by qualitative research, which similarly highlights mental health impacts for the unemployed as well as claimant groups such as lone parents and disabled people (Dwyer, Scullion, Jones, McNeill, & Stewart, 2020;Jamieson, 2020;Wright, Fletcher, & Stewart, 2020). In one such study, the authors detail "severe and acute negative emotional effects" (Wright & Stewart, 2016, p. 4) for JSA claimants following from both the threat and imposition of sanctions.…”
Section: Labour Market and Wider Impactsmentioning
confidence: 90%
“…The empirical investigation in this article focuses on developments in the period prior to the national rollout of UC, which oversaw a punitive shift in UK sanctions policy (Wright et al, 2020). This period is of substantive interest, since benefit sanction reforms made by the Coalition continue to underpin the enforcement of conditions within the contemporary social security system.…”
Section: Uk Policy Contextmentioning
confidence: 99%
“…If experienced positively, one could argue that increased supervision may lead to improved outcomes, especially compared to punitive measures such as incarceration and the withdrawal of welfare support. However, both criminal justice and welfare scholars have shown that punitive supervision can produce negative emotional and financial consequences (Edin and Shaefer, 2015;McNeill, 2019;Sherman, 2013;Wright et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Armed with this improved understanding of state drug ban policies, the second contribution of this paper is to provide the first known estimates of how variation in SNAP drug ban policies may be related to poverty. While proponents of new paternalism assert that increased supervision will reduce poverty by encouraging recipients to engage in work and treatment, a wealth of welfare research on work activation programs has shown that arduous supervision prompts people to simply forego needed government support (Raffass, 2017;Wright et al, 2020). In the case of drug bans, it is possible that increased supervision will lead to poverty if it is strenuous enough to deter people from applying for or from remaining in the program.…”
Section: Introductionmentioning
confidence: 99%